1860-1861 N.C. Sess. Laws 68 - (:unkn) unknown (My University, 1860)
Pub. Laws, ch. 34, § 1: Prohibited "any free negro" from wearing or carrying or keeping in his house any "any shot gun, musket, rifle, pistol, sword, sword cane, dagger, bowie knife, powder or shot."
Keywords: ENSLAVED PERSONS & OTHER MINORITIES